2015
DOI: 10.1177/2277975215595559
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Firm Performance on Board Characteristics: Empirical Evidence from India

Abstract: This study attempts to examine the impact of prior and current firm performance on board composition as it is the least explored issue in the corporate governance area. For this purpose, our analysis covers a large sample of the Indian manufacturing firms for the period 2001–2010. We utilize a range of measures of firm performance such as return on assets, return on equity, net profit margin, adjusted Tobin’s q and stock returns in the analysis. We also use a range of alternative measures of board characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 61 publications
5
15
1
Order By: Relevance
“…The study explores this relationship empirically, and uses board meeting, found that contradictory results of firms' performance parameters. This results with consistent of previous studies [32] …”
Section: Board Characteristics and Firm Performancesupporting
confidence: 94%
See 1 more Smart Citation
“…The study explores this relationship empirically, and uses board meeting, found that contradictory results of firms' performance parameters. This results with consistent of previous studies [32] …”
Section: Board Characteristics and Firm Performancesupporting
confidence: 94%
“…However, CEO duality, audit committee size, institutional shareholding and capital gearing ratio cannot be counted to explain the changes in financial performance because they are tested insignificance. To conclude, financial performance can be significantly and positively explained by the board size, board independence, board meeting frequency and firm size and same results is predicted by [32] [33] [34] [35]. Similarly, financial performance can be significantly and negatively explained by the audit committee independence and promoter shareholding and the constituent result with [8].…”
Section: Resultsmentioning
confidence: 67%
“…This study contradicts Uwuigbe and Fakile (2012) in studying influence of corporate governance in Nigerian financial sector found a mean of 13 board members and a standard deviation of 2.48. The study also contradicts Arora and Sharma (2015), who examined influence of board characteristics on corporate performance on the Indian firms found a mean of between 4 and 5 board size. Terjesen, Couto and Francisco (2015) evaluated impact of board size on firm performance in 47 countries globally found CV of 33.54 percent.…”
Section: Descriptive Statisticscontrasting
confidence: 65%
“…Surprisingly, it was found that audit committee characteristics negatively correlate with firms' performance during the financial crisis. Arora & Sharma (2015) examined the impact of Indian firms' performance on board directors' characteristics. It was found that firms' performance negatively impacts board characteristics.…”
Section: Literature Reviewmentioning
confidence: 99%